(untitled) (Journal of The Colloquium for Information Systems Security Education, 2014)
The smart grid initiative is working to modernize the North American electric power grid utilizing computing technologies in efforts to increase efficiency, reliability, and security [6, 16]. While the national energy infrastructure’s incremental evolution into a smarter grid continues to provide improvements, at the same time it is introducing security problems. The expanding adoption of the smart grid requires current and upcoming smart grid workforce to be aware of and understand specific security issues related to this domain. Educational institutions are frequently challenged to maximize existing resources for teaching the required curriculum, often leaving little to no resources available for teaching specialized courses such as smart grid security. The use of technologies for education provides a cyberlearning environment option for maximizing limited resources. To address the increasing national demand for smart grid security education, Cyberlearning Environment about Smart Grid Security (CySGS) was created to serve as an educational resource for the security community.